2017
DOI: 10.9789/2175-5361.2017.v9i2.327-332
|View full text |Cite
|
Sign up to set email alerts
|

As necessidades de cuidado do cliente oncológico hospitalizado: aplicação da taxonomia nanda Care needs of hospitalized cancer patients: application of nanda taxonomy

Abstract: | Brito KCFV; Souza SR | Care needs of hospitalized... As necessidades de cuidado do cliente oncológico hospitalizado: aplicação da taxonomia nanda ABSTRACTObjectives: To identify care needs of cancer patient and correlate these needs with the domains of NANDA taxonomy. Method: Qualitative study conducted in clinical wards for hospitalization of adults of a university hospital in Rio de Janeiro. Seven interviews were conducted and analyzed by the method of thematic analysis. Results: The interviews showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Muitos pacientes e seus familiares, no momento do diagnóstico, sentem um impacto psicossocial e possuem como primeira concepção a morte, pois a doença já traz consigo esse estigma. Seus projetos quanto ao futuro ficam incertos, sendo então revelados sentimentos de medo, sofrimento, constrangimento, negação, tristeza, apreensões, dúvidas e até sentimento de impotência e, desta forma, aspectos emocionais e psicológicos relacionados à depressão e ansiedade podem ocorrer durante este processo repercutindo negativamente na qualidade de vida do homem [12][13][14] .…”
Section: Discussionunclassified
“…Muitos pacientes e seus familiares, no momento do diagnóstico, sentem um impacto psicossocial e possuem como primeira concepção a morte, pois a doença já traz consigo esse estigma. Seus projetos quanto ao futuro ficam incertos, sendo então revelados sentimentos de medo, sofrimento, constrangimento, negação, tristeza, apreensões, dúvidas e até sentimento de impotência e, desta forma, aspectos emocionais e psicológicos relacionados à depressão e ansiedade podem ocorrer durante este processo repercutindo negativamente na qualidade de vida do homem [12][13][14] .…”
Section: Discussionunclassified
“…The global nursing research literature has repeatedly shown that nurses' use of empathic communication has numerous patient benefits. For example, empathic communication helps circumvent dehumanizing treatment of patients with Alzheimer's disease, 1 enables cancer patients to cope more effectively with their illness, 2 leads patients to take greater autonomy in their care, 3 reduces symptoms of chronic pain and irritable bowel syndrome, 4 improves patient satisfaction with their quality of life, 4 and reduces anxiety, distress, and depression 4 …”
mentioning
confidence: 99%